PENGARUH LIVE STREAMING DAN FEAR OF MISSING OUT TERHADAP KEPUTUSAN PEMBELIAN - Siti Rahma Nurhafizah; Eti Arini (Yayasan Insani Mandiri Santani, 2026)
This study aims to analyze the effect of Live Streaming and Fear of Missing Out (FoMO) on the purchase decisions of Generation Z TikTok Shop users among students at Muhammadiyah University of Bengkulu. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 301 respondents. The data analysis technique used is multiple linear regression analysis with the assistance of SPSS software. The results of this study indicate that Live Streaming has a positive and significant effect on the purchase decisions of student TikTok Shop users at Muhammadiyah University of Bengkulu. Fear of Missing Out (FoMO) also has a positive and significant effect on purchase decisions. The higher the attractiveness, trust, and expertise in live streaming, as well as the higher the level of FoMO experienced, the greater the tendency of students to make purchase decisions. Simultaneously, Live Streaming and Fear of Missing Out (FoMO) have a positive and significant effect on purchase decisions. Therefore, improving the quality of live streaming and leveraging the FoMO phenomenon can enhance students' purchase decisions. Keywords: live streaming, fear of missing out (FoMO), purchase decision.